2021
DOI: 10.1002/pc.25994
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nanoclay loading on the structural, thermal and dielectric properties of montmorillonite/polypropylene nanocomposites

Abstract: The morphological, thermal and electrical properties of nanocomposites based on polypropylene (PP) filled with 2 wt% and 6 wt% of organo-clay montmorillonite (MMT) were studied in this research. X-ray diffraction show an increase of the inter-lamellar distance indicating that PP chains have been well intercalated in the galleries of the montmorillonite. Transmission electron microscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Also, in Figure 8A,B, compared with PSMCC, there was a significant increase in dielectric constant and dielectric loss with increasing MMT clay filler and decreased with the increase of frequency. This increase is noticed, indicating a rise of the material polarizability after the addition of MMT 55 . At 5 wt% MMT clay concentration, it was found that έ values decreased compared to 1 and 3 wt% MMT clay concentrations due to the increase of exfoliated structures at these MMT clay concentrations in the polymer matrix, while the predominance of intercalated clay increases these values 56 .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Also, in Figure 8A,B, compared with PSMCC, there was a significant increase in dielectric constant and dielectric loss with increasing MMT clay filler and decreased with the increase of frequency. This increase is noticed, indicating a rise of the material polarizability after the addition of MMT 55 . At 5 wt% MMT clay concentration, it was found that έ values decreased compared to 1 and 3 wt% MMT clay concentrations due to the increase of exfoliated structures at these MMT clay concentrations in the polymer matrix, while the predominance of intercalated clay increases these values 56 .…”
Section: Resultsmentioning
confidence: 87%
“…The variation of the (A) dielectric constant, (B) dielectric loss and (C) electrical conductivity with frequency for pure PSMCC and nanocomposite films with MMTF I G U R E 9The conductivity of PSMCC/MMT nanocomposite films for different weight percent of MMT at 10 kHz Also, in Figure8A,B, compared with PSMCC, there was a significant increase in dielectric constant and dielectric loss with increasing MMT clay filler and decreased with the increase of frequency. This increase is noticed, indicating a rise of the material polarizability after the addition of MMT 55. At 5 wt% MMT clay concentration, it was found that έ values decreased compared to 1 and 3 wt% MMT clay concentrations due to the increase of exfoliated structures at these MMT clay concentrations in the polymer matrix, while the predominance of intercalated clay increases these values.56 The έ values of these nanocomposites increase again and reach their maximum at 10 wt% MMT clay concentration; 10 wt% clay loading increased έ values approximately 1.5 times than PSMCC film without MMT clay at a fixed frequency.…”
mentioning
confidence: 83%
“…Clay is a naturally occurring nanomaterial of huge interesting properties and a wide range of technological applications [15][16][17][18][19]. Therefore, the nanoclay and polymer matrices based PNC materials exhibited outstanding properties like environmental stability, controllable flexibility, cost-effectiveness, reduced flammability, high barrier resistance as well as tailored nanodielectric behaviour [15,16,18,20,21]. Several studies explored the potential uses of polymer/clay nanocomposite materials in food packaging, electromagnetic interference (EMI) shielders, in improving the aerospace, agricultural, and automotive technologies, and also developing flexible and high performance optoelectronic, microelectronic, and energy storage devices [6,15,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…5,6,[9][10][11] In addition to the alterations in chemical and thermomechanical properties of the PNCs, it is also observed that the dielectric and electrical properties of nanoclay loaded polymer matrices are largely affected by the intercalated/exfoliated clay structures. 4,7,12,13,[16][17][18][19][20][21] However, most of the dielectric studies on the clay containing PNCs were performed with externally applied electric field starting from frequency of a few millihertz or hertz and extending up to some megahertz. It is because of the fact that the interfacial polarization largely contributes to the dielectric permittivity in all types of hybrid nanocomposites at lower frequencies which is imperative for exploring their nanodielectric applications in low-frequency device technologies.…”
Section: Introductionmentioning
confidence: 99%
“…It is because of the fact that the interfacial polarization largely contributes to the dielectric permittivity in all types of hybrid nanocomposites at lower frequencies which is imperative for exploring their nanodielectric applications in low-frequency device technologies. 4,13,[16][17][18][19][20][21][22][23][24][25][26] However, dielectric properties of PNCs in the high to ultrahigh frequency range of harmonic electric field are less attempted due to several complex measurement protocols, although, the dielectric parameters in this range are in high industrial demand in order to select appropriate composite materials in developing promising radio-electronic devices and other technological uses. [27][28][29][30][31][32][33] Thus, in this manuscript, we report the dielectric dispersion behavior and alternating current (AC) electrical conductivity of the PEO/OMMT nanocomposites in the radio frequency range of 1 MHz-1 GHz, and also the OMMT structural properties and thermal behavior of PEO crystallites.…”
Section: Introductionmentioning
confidence: 99%